Sentence Connectors in The Lyrics of Songs of Red Album by Taylor Swift - Muhammad, Hassan (The Explora, 2022)
This study deals with the use of Sentence Connectors, Coordinating Conjunction in Red album by Taylor Swift. The objective of this study were to describe the types of coordinating conjunction, to find out the most dominant and the reason for using thet dominant types in that album. The source of data was Red album and the script. This study applied descriptive qualitative method. The data were classified into types of the coordinating conjunction. They were analyzed based on the types of coordinating conjunction. The study found that there are seven types of coordinating conjunction, they are for, and, nor, but, of, yet, so. There are 299 coordinating conjunction in that album. The percentages of coordinating conjunction found were for is 16 (6. 35%), and is 173 (57. 86), nor is 0 (0%), but is 50 (16.72%), of is 46 (15. 38), yet is 0 (0%), so is 14 (4.7%). The dominant types of coordinating conjunction found in Red album is and, 173 items (57. 86% ).